Sutureless Transconjunctival Insertion of Eyelid Weights: A Novel Technique. Issue 1 (8th November 2021) - Elahi, Ebby; Afshin, Evan E.; Guthrie, Ashley J.; Lo, Christopher
Abstract : Purpose: To describe a novel surgical technique for implanting eyelid weights via a sutureless transconjunctival approach. In comparison to the traditional supratarsal crease approach, this technique does not involve any external incisions or suture placement. The procedure can reduce surgical time and complications associated with the traditional external approach. Methods: This case series includes 13 patients who underwent eyelid weight placement via the transconjunctival approach for paralytic lagophthalmos secondary to facial nerve paralysis (12 patients had unilateral paralysis and 1 patient had bilateral) with a total of 14 eyelid weights placed. The procedures were performed at an outpatient office-based surgical center. All procedures were performed or supervised by the same surgeon. Patients were followed for an average 6-month postoperative period for postoperative complications. Results: The sutureless transconjunctival approach to eyelid weight insertion was successful in achieving the desired functional and aesthetic outcomes. Patients undergoing this technique avoided the discomfort of postoperative suture removal. All patients achieved comparable outcomes postoperatively. There were no complications reported across the 13 patients throughout the 6-month postoperative period. Conclusions: This case series demonstrates that the transconjunctival approach for metal eyelid weight insertion is practical, relatively easy to perform, and associated with functional outcomes that are comparable to those achieved with the traditional approach, however, without external incision or placement of sutures. Abstract : The authors describe a new transconjunctival approach to eyelid weight insertion that produces desirable functional and aesthetic outcomes in the treatment of lagophthalmos and overcomes some of the challenges posed by traditional techniques.